2022
DOI: 10.23917/jramathedu.v7i3.16784
|View full text |Cite
|
Sign up to set email alerts
|

A constructivist analysis of Grade 8 learners’ errors and misconceptions in simplifying mathematical algebraic expressions

Abstract: Algebra is an important branch of mathematics which applies to many fields related to mathematics. However, many studies show algebra as posing problems even to the most gifted students. This phenomenon, therefore, necessitates more studies to be conducted in this area. As such, the study explored the types of errors that Grade 8 learners committed in simplifying algebraic expressions and the misconceptions that might have given rise to such errors. Ninety-five Grade 8 learners were selected as the subjects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Persistent errors and misconceptions in addition and subtraction of directed numbers Misconceptions are unavoidable stages in the learning process (Moru & Mathunya, 2022). The result that the misconception leads to persistent errors has been shared by the several studies, for example, Iddrisu et al (2017) and Moru and Mathunya (2022). In the study conducted by Aydin-Guc and Aygun (2021) and Kim et al (2016), it was reported that the students made a reversal error where they map the order of words from the question.…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…Persistent errors and misconceptions in addition and subtraction of directed numbers Misconceptions are unavoidable stages in the learning process (Moru & Mathunya, 2022). The result that the misconception leads to persistent errors has been shared by the several studies, for example, Iddrisu et al (2017) and Moru and Mathunya (2022). In the study conducted by Aydin-Guc and Aygun (2021) and Kim et al (2016), it was reported that the students made a reversal error where they map the order of words from the question.…”
Section: Literature Reviewmentioning
confidence: 97%
“…This was followed by the advantage and disadvantages of argumentation and indigenous language used in learning and teaching of mathematics. Persistent errors and misconceptions in addition and subtraction of directed numbers Misconceptions are unavoidable stages in the learning process (Moru & Mathunya, 2022). The result that the misconception leads to persistent errors has been shared by the several studies, for example, Iddrisu et al (2017) and Moru and Mathunya (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The constructivists argue that learners bring into the classroom concepts they may be using outside the classroom. As pointed out by Moru and Mathunya (2022), learners do not come to class as empty vessels; rather, they bring with them prior knowledge from previous classes and other interactions with the environment. In this view, as they communicate in an informal manner on WhatsApp out of classrooms, the language used on this platform is then internalized and reproduced by them in their academic essays.…”
Section: The Constructivist Notion Of Error Analysismentioning
confidence: 99%
“…The persistent use of social media language by learners also indicate that teachers should develop skills in analysing learners' errors. Teachers should be able to identify, diagnose and remedy errors learners frequently commit (Moru & Qhobela, 2013;Moru et al, 2014;Moru & Mathunya, 2022). Once the diagnosis is posed, remediation should be carried out by teachers (Booth et al, 2014;Makonye, 2016;Makonye & Fakude, 2016).…”
Section: Conclusion: the Way Forwardmentioning
confidence: 99%